A new model of land system in ukraine with regard to the local government reform - Tretiak, A.; Tretiak, V.; Panchuk, O. (Land Management, Cadastre and Land Monitoring, 2017)
During the implementation of land reform in independent Ukraine land system changed twice. Today, due to the decentralization of power is his search for a new model for the future, as outlined in this study. Also note that when we formulated the concept refers to the land system - land system, ie a set of measures for the territorial organization of land and other natural resources, land relations, defined system of ownership and use of land, as well as the principles of the territory. In order to put scientifically based proposals improving the organization and functioning of an effective system of land versatile conceptual model of land system of Ukraine, which includes four functional blocks, namely:1) land system for natural and economic zoning (zoning); 2) land system for administrative-territorial division; 3) land structure by ownership of land; 4) land structure on the forms and methods of land use (types (subtypes) of land). Proved that: 1) constitutional definition of administrative-territorial division of Ukraine and strengthening forms of land ownership - private, communal and public, with subsequent legal registration in the Land Code of Ukraine (2001) resulted in the elimination territory of village, town and city councils as the basic foundations Business and financial stability of local communities. Not conducting land works on delimitation of state and municipal property (as of 01.01. 2017 communal lands account for 0.5% of the total area of the country in predictable areas 25-28%) and deprivation in 2012. councils powers to manage state-owned land within settlements, along with the elimination of area councils, led to corresponding changes in land structure of Ukraine and elimination of local communities and land-management pryrodokorystu¬vannyam that had a negative impact on quality of life and Security EKU population for sustainable development forms of land use in rural areas. 2) The system of conceptual positions and measures on administrative-territorial reform and the creation of an effective system versatile land and sustainable land use inUkrainein the future should be based on the proposed model of land system ofUkraine. 3) Reconciliation measures of reform the land system ofUkraineand the administrative-territorial caused minor actual results of the latter and non potential of land and other natural resources of local communities in their territories (used only in agriculture by 39% and in other areas of 1 to 50%). Keywords. Land system, administrative-territorial system, form of land ownership, form of land use, model of new land system